Comparison of the effectiveness of the schema therapy package based on psychosocial issues of obsessive-compulsive patients with cognitive-behavioral therapy on early maladaptive schemas and anxiety in patients with obsessive-compulsive disorder - Aflakian, Mehdi; Atashpour, Hamid; Khayatan, Flora (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: obsessive-compulsive disorder is a debilitating anxiety disorder whose main feature is the occurrence of obsessions and compulsive actions. The purpose of this study is to compare the effectiveness of the schema therapy package based on psycho-social issues of obsessive-compulsive patients with cognitive-behavioral therapy on early maladaptive schemas and anxiety in patients with obsessive-compulsive disorder. Methods: This article was a semi-experimental method, pre-test-post-test type with a control group and a 45-day follow-up period. The research population in this study included all patients with obsessive-compulsive disorder who referred to two psychotherapy clinics in Isfahan city. For the study, 45 people were randomly selected into two groups of schema therapy based on psychosocial issues (based on Yang, Kliusko and Wishar, 2003), cognitive-behavioral therapy (Struch et al., 2007) and a control group (each group). 15 people) were placed. Before and after the intervention and 45 days later (follow-up stage), the subjects responded to the short-form Young’s schema questionnaire (Young, 1994) and the anxiety questionnaire (Beck, 1989). The data was analyzed using the method of analysis of variance with repeated measurements and Spss.22 software. Results: The results of the study showed that there is a significant difference in the mean of early maladaptive schemas and anxiety in two experimental groups (schema therapy and cognitive-behavioral therapy) and evidence. In addition, based on the results of schema therapy compared to cognitive-behavioral therapy, in the reduction of early maladaptive schemas (F=33.06; P<0.001) and anxiety (F=11.26; P<0.001) Patients were more effective. Conclusion: Compared to cognitive-behavioral therapy, schema therapy treatment based on psycho-social issues can play an effective role in reducing the early maladaptive schemas and anxiety of these patients.